Bioinspired MXene‐Based Piezoresistive Sensor with Two‐stage Enhancement for Motion Capture (Adv. Funct. Mater. 18/2023). (2nd May 2023) - Wang, Shenglong; Deng, Weili; Yang, Tao; Ao, Yong; Zhang, Hongrui; Tian, Guo; Deng, Lin; Huang, Haichao; Huang, Junfeng; Lan, Boling; Yang, Weiqing
Abstract : Bioinspired Intermittent Designs In article number 2214503, Weiqing Yang, Weili Deng, and co‐workers present a strategically designed villus‐inspired intermittent architecture that can enhance the piezoresistive performance through a laser‐induced manufacturing process. By utilizing the two‐stage enhancement of intermittent pillars, the device shows a 20 times increase in sensitivity and 5 times increase in response range than conventional homogeneous microstructures. It represents a significant step forward in the development of commercial bioelectronics.